Fracture and Pseudoarthrosis of the Giant Os Trigonum (Revista de Medicina Clinica, 2025)
Os Trigonum is the consequence of a lack of fusion of the lateral tubercle of the posterior process of the talus with the body of the talus, or of a fracture of a partially or completely ossified centrum. Present in between 1.7% and 25% of the population, it was first described by Rosenmüller in 1804. Giant os trigonum is a rare entity, and its fracture and pseudoarthrosis are even rarer, which increases the possibility of causing painful symptoms, caused by the “nutcracker” effect. X-rays and magnetic resonance imaging are the diagnostic aids for characterizing this entity.
Keywords: Astragalus; Os fracture; Pseudoarthrosis